Mediacja w percepcji nieletnich wychowanków zakładów poprawczych – doniesienia z badań własnych - Cwalina, Małgorzata (Wydawnictwo Naukowe UAM, 2013)
The article presents mediation proceedings applied in juvenile court cases in Poland. It is based on my master’s thesis entitled: Mediation as a method of protection of juveniles against stigmatization. The article is divided into two sections. The first one depicts the fundamental assumptions of mediation process, the second contains a description and analysis of my own research carried out among young people from half-open penitentiaries in the region of Mazovia.
The perception of mediation amongst juveniles in reformatories
Keywords: mediation; juvenile; restorative justice